DATA-WARE OF PRECISION ATTITUDE AND HEADING REFERENCE SYSTEM - Sushchenko, Olha (Proceedings of National Aviation University, 2018)
Purpose: The paper focuses on features of data-ware of precision attitude and heading reference systems, which can be applied in the high-precision applications, for example, navigation of marine vehicles. The main goal is to create the data-ware adapted to functioning of the multi-mode navigation system. Methods: To solve the given problem the methods of the inertial navigation, automatic control theory including servo systems and methods of statistical processing of information are used. Results: The data-ware of the precision attitude and heading reference system is developed taking into consideration different modes of the system and interrelation between them. The basic expressions of data-ware for the high precision multimode attitude and heading reference system are obtained. The general block-scheme of operating algorithm of the system is given. Conclusions: The results of development of data-ware of the precision attitude and heading reference system taking into consideration presence of some operating modes are represented. Obtained results can be useful for design of precision navigation systems of the moving vehicles of the wide class.